Somatostatin modulates insulin-degrading-enzyme metabolism: implications for the regulation of microglia activity in AD. - Grazia Tundo (Public Library of Science (PLoS), 2012)
The deposition of β-amyloid (Aβ) into senile plaques and the impairment of somatostatin-mediated neurotransmission are key pathological events in the onset of Alzheimer's disease (AD). Insulin-degrading-enzyme (IDE) is one of the main extracellular protease targeting Aβ, and thus it represents an interesting pharmacological target for AD therapy. We show that the active form of somatostatin-14 regulates IDE activity by affecting its expression and secretion in microglia cells. A similar effect can also be observed when adding octreotide. Following a previous observation where somatostatin directly interacts with IDE, here we demonstrate that somatostatin regulates Aβ catabolism by modulating IDE proteolytic activity in IDE gene-silencing experiments. As a whole, these data indicate the relevant role played by somatostatin and, potentially, by analogue octreotide, in preventing Aβ accumulation by partially restoring IDE activity.